Association between physical activity, sedentary time, participation in organized activities, social support, sleep problems and mental distress among adults in Southern Norway: a cross-sectional study among 28,047 adults from the general population - Tonje Holte Stea; Susanne Aune Solaas; Annette Løvheim Kleppang (BMC, 2022)
Abstract Background Identification of modifiable factors associated with poor mental health is crucial to develop targeted and effective intervention strategies for prevention of mental distress and illness in the general population. Thus, the aim of the present study was to examine the association between low level of leisure-time physical activity, high sedentary time, low participation in organized activities, low social support, sleep problems, and mental distress in a large sample of Norwegian adults. Methods A cross-sectional study was completed by 28,047 adults (≥18 years old) in southern Norway by filling out an online self-report questionnaire. Multivariable binary logistic regression models, stratified according to gender and adjusted for age and perceived financial situation, were used to examine possible associations between unhealthy lifestyle behaviors, participation in organized activities, social support, and mental distress. Results Our results showed an increased odds of having mental distress among men reporting low leisure-time physical activity (OR: 1.18; 95%CI: 1.03-1.37), high sedentary time (1.32; 1.16-1.51), low involvement in organized activities (1.43; 1.25-1.64), low social support (2.55; 2.18-2.99), and sleep problems (7.29; 6.35-8.37) compared to the rest of the male population. For women, the results showed increased odds of mental distress among those reporting high sedentary time (1.25; 1.11-1.39), low involvement in organized activities (1.60; 1.42-1.80), low social support (2.71; 2.39-3.06), and sleep problems (5.78; 5.15-6.50) compared to the rest of the female population. For both men and women, results also indicated that mental distress was increased among younger adults and among those reporting financial difficulties compared to the rest of the population. Conclusion Our results showed an association between unhealthy lifestyle behaviors, low participation in organized activities, low social support and mental distress, and that the strength of the association varied substantially. These findings provide increased knowledge about the relationship between modifiable lifestyle factors and mental health which should have implications for future public health efforts.